The Psychology of Money: Pelajaran Abadi Mengenai Kekayaan, Ketamakan, dan Kebahagiaan - Ayu Safitri; Putri Rizky Apriyani; Shen Fuwi (Yayasan Aya Sophia Indonesia, 2024)
This study aims to review the contents of a book entitled